The Concept of Sustainable Groundwater Management in Supporting Industrial Estates - Ghina Amalia; Budi Heri Pirngadi; M. Zaenal Ramdhani A. Siddiq (School of Postgraduate Studies, Diponegoro Univer, 2025)
Water needs in industrial areas can be met by using surface water and groundwater sources. However, this can cause its own problems for the region due to increased water demand. The area of the industrial area in Sumberjaya Sub-district which reaches 329,700 m² will require water for industry amounting to 8,534,678 m3/ year, with no direction in sustainable groundwater management it is feared that it will have an impact on the loss of groundwater resources and the occurrence of a crisis or scarcity of water resources. This research aims to find out directions in sustainable groundwater management that are appropriate, integrated, and can be applied to supporting industrial estates in Sumberjaya District, Majalengka Regency. This analysis was conducted using descriptive qualitative and descriptive quantitative approaches. We conducted this analysis using observation, interview, and secondary data collection methods. The analysis method in this research is the calculation method of rainwater harvesting (PAH) and the calculation of the recharge concept. From the results of the analysis of the potential and problems that exist in Sumberjaya Subdistrict, in helping to fulfil industrial water needs other than groundwater, can apply concept direction in groundwater conservation using the Rainwater Harvesting calculation method and recharge wells.